THE MANAGEMENT OF A PROJECT FOR THE IMPROVEMENT OF THE SERVICES QUALITY IN THE TOURISM SECTOR – THE CERTIFICATION EMAS/ECOLABEL OF A TOURISTIC STRUCTURE IN THE SOUTH ITALY - Arianna Di Vittorio; Pierluigi Passaro (European Scientific Journal, ESJ, 2014)
The environmental politics has assumed in the last times a wide and transversal dimension, focused on the problems and the relationships of a complicated system such as the environment, in whose inner different elements interact and put problems of bilance and disbalance. With the new Strategy, the European Community means to pursue the integration of objectives of environmental sustainability (Goteborg Agenda) with those of the economical and social development (Lisbon Agenda), the environmental politics integrate therefore substantially to the problematics of social- economical development. The adoption of eco-management systems, from a relevant number of firms also in the touristic sector and their certification according to international and european standards represents an important element of innovation, following this strategy aimed to conjugate the development with the environment protection. The systems of environmental management have by now become a distinctive element of the companies which want to cover a relevant role in the competitive national and international scenery, even because their nature itself makes them verifiable from independent third subjects, and suitable to stimulate the continuous development of the environmental and productive performances. Object of the present work is the analysis of the management of a project for the improvement of services quality in the tourism sector, which allows to obtain the certification Emas/Ecolabel in a touristic structure in the south of Italy.